Four new species of Sabatieria Rouville, 1903 (Nematoda, Comesomatidae) from the Continental Slope of Atlantic Southeast - Botelho, Alessandra Prates; Da Silva, Maria Cristina; Esteves, André Morgado; Fonsêca-Genevois, Verônica (Zootaxa, 2007)
Sabatieria is the most abundant genus along the Campos Basin, Rio de Janeiro (Brazil). Four new species of Sabatieria (Nematoda-Comesomatidae) from the Continental Slope of Atlantic Southeast are described. Sabatieria spiculata sp.nov. is characterized by the size of spicule and the presence of dorsal tooth ; S. paraspiculata sp. nov. by tail shape and the maximum diameter; S. bitumen sp. nov. by spicule shape with an arrow-like distal part and the S. subrotundicauda sp.nov. by a round tail and reflected ovary.